Central Bank communication and the perception of monetary policy by financial market experts - Schmidt, Sandra; Nautz, Dieter (Journal of money, credit and banking, 2012)
This paper investigates how financial experts perceive the monetary policy of the European Central Bank (ECB). Assuming a Taylor-rule-type reaction function, we use qualitative survey expectations about future interest rates, inflation, and output to discover the sources of individual interest rate forecast errors. Based on a panel random coefficient model, we show that financial experts have systematically misperceived the ECB’s interest rate rule. While perception of monetary policy regarding inflation has become more accurate since the ECB’s clarification of the monetary policy strategy in 2003, misperception regarding the ECB’s reaction to output has increased in the financial crisis.